The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1051/meca/2014048
|View full text |Cite
|
Sign up to set email alerts
|

Thermohydrodynamic analysis of a textured sector-pad thrust bearing: effects on mechanical deformations

Abstract: -In this paper, a computational investigation of thermohydrodynamic performance and mechanical deformations of a fixed-geometry thrust bearing with artificial surface texturing is presented. A parallel eight-pad bearing is considered; the surface of each pad is partially textured with square dimples. Here, a CFD-based thermohydrodynamic modeling approach, recently introduced by the authors, is used to calculate the performance of the bearing; the THD results are then used to quantify the deformations of the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…However, texturing both surfaces resulted in additional improvement. Based on CFD approaches by solving the Navier-Stokes equations as well as the energy equation in the fluid and heat transfer equation in the pads, Papadopoulos et al [40][41][42][43] showed a considerable increase of the load-carrying capacity only for lower to moderate sliding velocities, while the improvement was reduced for higher velocities. However, the partially textured linear plain bearing exhibited lower friction due to the lower lubricant film height.…”
Section: Parallel Hl Contactsmentioning
confidence: 99%
“…However, texturing both surfaces resulted in additional improvement. Based on CFD approaches by solving the Navier-Stokes equations as well as the energy equation in the fluid and heat transfer equation in the pads, Papadopoulos et al [40][41][42][43] showed a considerable increase of the load-carrying capacity only for lower to moderate sliding velocities, while the improvement was reduced for higher velocities. However, the partially textured linear plain bearing exhibited lower friction due to the lower lubricant film height.…”
Section: Parallel Hl Contactsmentioning
confidence: 99%
“…In 2011, Papadopoulos et al [13] presented an optimization study where they used a CFD code to solve the Navies-stokes and energy equations; the authors neglected the effects due to the cavitation. The optimization goal is the maximization of the bearing load carrying capacity.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of certain textured features is known to may benefit some lubricant systems by acting as microreservoirs, storing and providing the fluid directly to the contact zone. The use of a textured bearing system has been found to be more demanding due to its advantageous features such as low value of friction, higher load carrying capacity, decreasing surface damages and increasing service life of bearing [11,12]. In the recent year, many bearing designers focused on the influence of surface texture in the fluid film journal bearing system.…”
Section: Introductionmentioning
confidence: 99%